Albuminuria, serum antioxidant enzyme levels and markers of hemolysis and inflammation in steady state children with sickle cell anemia. Issue 1 (December 2016) - Itokua, Karen; Makulo, Jean; Lepira, François; Aloni, Michel; Ekulu, Pépé; Sumaili, Ernest; Bukabau, Justine; Mokoli, Vieux; Longo, Augustin; Kajingulu, François; Zinga, Chantal; Nlandu, Yannick; et al.
Abstract Background Oxidative stress is thought to be involved in the pathogenesis of microalbuminuria in Sickle cell anemia (SCA). Antioxidant enzymes such as glutathione peroxidase (GPx) and Cu-Zn superoxide dismutase (SOD) may play an important protective role. This study aimed to evaluate the association between albuminuria and these two antioxidant enzymes. Methods We consecutively recruited Steady state children aged between 2 and 18 years old with established diagnosis of homozygous SCA in two hospitals of Kinshasa/DR Congo. The relationship between Urinary Albumin Creatinine Ratio (UACR) and other variables of interest (age, systolic blood pressure, diastolic blood pressure, plasma GPx and Cu-Zn SOD, free plasmatic hemoglobin, LDH, indirect bilirubin, white blood cells (WBC), percentage of fetal hemoglobin, serum iron, ferritin, CRP) was analyzed by Bivariate correlation (Pearson's correlation coefficient). Microalbuminuria was defined by urine albumin/creatinine ratio between 30 and 299 mg/g. Results Seventy Steady state Black African children with SCA (56% boys; average age 9.9 ± 4.3 years; 53% receiving hydroxyurea) were selected. Prevalence of microalbuminuria was 11.8%. LDH (r = 0.260;p = 0.033) and WBC count (r = 0.264;p = 0.033) were positively correlated with UACR whereas GPx (− 0.328;p = 0.007) and Cu-Zn SOD (− 0.210;p = 0.091) were negatively correlated with UACR. Conclusions Albuminuria is associated with decreased antioxidant capacity and increased levels of markers of hemolysis and inflammation. Therefore, strategies targeting the reduction of sickling and subsequent hemolysis, oxidative stress and inflammation could help preventing or at least delaying the progression of kidney disease in SCA children.